Perfil sorológico e oxidativo de gestantes recebendo tratamento para infecção pelo Toxoplasma gondii e acompanhamento dos resultados perinatais - Paula, Hellen Lopes de (2022)
Toxoplasmosis is a worldwide pathology, caused by the protozoan Toxoplasma gondii (T. gondii), which can affect humans at any period of life, however, it becomes extremely relevant when it affects women for the first time during pregnancy. The disease in this period, in most cases without clinical manifestations, can lead to fetal involvement, causing complications. Among the main factors involved in the pathophysiology of diseases, including toxoplasmosis, oxidative stress stands out. Therefore, this study aimed to verify in pregnant women diagnosed and treated for T. gondii infection, possible changes in immunological, clinical and oxidative parameters, as well as to evaluate the perinatal results. The study included 27 pregnant women belonging to the control group, and 55 with the disease, of which 42 confirmed the acute phase and 26 used the triple regimen (sulfadiazine, pyrimethamine and folinic acid - SPFA) as treatment, and the groups consisted of this description. Samples and data were collected from February 2017 to September 2019. Participants with toxoplasmosis were infected during the 2018 outbreak in the city of Santa Maria, Rio Grande do Sul, Brazil. The immunological criteria were evaluated through the detection of immunoglobulin M (IgM) and immunoglobulin G (IgG), as well as IgG avidity test, being related to the symptomatology. The analysis of the general condition was performed by clinical and laboratory parameters. Oxidative stress was determined by the quantification of oxidative damage markers (thiobarbituric acid reactive substances (TBARS) and nitric oxide (NO)), as well as oxidative stress protectors (protein (P-SH) and non-protein (NP-SH) thiols groups, vitamin C, plasma iron reduction capacity (FRAP)), in addition to the verification of the activity of the enzyme δ-aminolevulinate dehydratase (δ-ALA-D). Perinatal outcomes were assessed by the degree of clinical impairment of newborns through analysis of medical records. The maternal serological response was heterogeneous, with higher levels of IgM antibodies among pregnant women who had symptoms at the time of diagnosis. In some pregnant women, lower levels of IgM were found, not always accompanied by low IgG avidity, despite the diagnosis of acute infection, differing from the expected classic serological profile. The treatment instituted at the time of detection of the disease, for all pregnant women, allowed only three newborns to present the congenital form. The damage marker parameters (TBARS and NO), as well as most antioxidants (P-SH, NP-SH and FRAP) and δ-ALA-D enzyme activity, were higher in pregnant women with the disease, indicating that the pharmacological treatment received may have stimulated a protective compensatory response. From this study, there was an increase in information in the literature on the subject, emphasizing the need for new biomarkers, as well as reinforcing the importance of instituting and maintaining treatment.